2006
DOI: 10.2308/accr.2006.81.1.113
|View full text |Cite
|
Sign up to set email alerts
|

Are Investors Influenced by Pro Forma Emphasis and Reconciliations in Earnings Announcements?

Abstract: This study presents the results of an experiment that examines how two underlying characteristics of pro forma earnings announcements, pro forma emphasis and the presence of a quantitative reconciliation, influence nonprofessional investors' and analysts' reliance on pro forma disclosures. The results indicate that the emphasis management places on pro forma earnings, not the mere presence of pro forma earnings, influences nonprofessional investors' judgments and decisions, but that this influence is mitigated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
108
1
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 301 publications
(127 citation statements)
references
References 28 publications
9
108
1
1
Order By: Relevance
“…Low Elliott (2006) In an experiment, participants made earnings potential judgments and an investment decision based on an earnings release that reported only GAAP earnings, emphasized either GAAP or pro forma earnings or provided a reconciliation of GAAP and pro forma earnings. Frederickson and Miller (2004) In an experiment, participants made stock price judgments based on an earnings release that reported only GAAP earnings or that reported both GAAP and pro forma earnings.…”
Section: Lowmentioning
confidence: 99%
“…Low Elliott (2006) In an experiment, participants made earnings potential judgments and an investment decision based on an earnings release that reported only GAAP earnings, emphasized either GAAP or pro forma earnings or provided a reconciliation of GAAP and pro forma earnings. Frederickson and Miller (2004) In an experiment, participants made stock price judgments based on an earnings release that reported only GAAP earnings or that reported both GAAP and pro forma earnings.…”
Section: Lowmentioning
confidence: 99%
“…If they do not include CI in their ratio analysis, the presentation format might still affect their judgements about the firm's financial condition and profitability. Regardless of the usefulness of the information, its salience or prominence can affect how users weight it during the decision process (Dreben et al, 1979;Duncan, 1980;Elliott, 2006;Russo, 1977).…”
Section: Rq: Do Nonprofessional Investors Use CI In Their Financial Cmentioning
confidence: 99%
“…Each scenario also included a positive (actuarial gain) or negative (actuarial loss) OCI item. As in prior research, MBA students were used as proxies for nonprofessional investors (Maines and McDaniel, 2000;Frederickson and Miller, 2004;Hodge et al, 2004;Elliott, 2006;Fortin and Berthelot, 2012). In fact, Elliott et al (2007) established that second-year MBA students enrolled in or having completed a financial statement analysis course make good proxies for nonprofessional investors in tasks relatively low in integrative complexity.…”
Section: Design and Participantsmentioning
confidence: 99%
“…Financial reporting is the most important instruments for all companies to disclose the performance and the company condition to investors, regulators, and employees (Elliott, 2006). Shah and Butt (2011) said that although the accounting system had already worked to create strict rules to make the information presented reasonable, there were still many areas that could be developed to give description based on the company interest to the financial reports users.…”
Section: Introductionmentioning
confidence: 99%
“…The manager is supposed to use company reports as a means of impression management to strategically manipulate the perceptions and decisions of stakeholders (Yekini, Wisniewski, & Millo, 2016). The concept of impression management applied in the context of the company report of the company is to analyze the efforts to influence the stakeholder perceptions toward the organization especifically financial performance as described by Clatworthy and Jones (2001;2003;2006) and Courtis (2004), and environment social performance (Hooghiemstra, 2000). Bolino, Kacmar, Turnley, and Gilstrap (2008) showed that managers used various impression management techniques in the narrative part of the annual report.…”
Section: Introductionmentioning
confidence: 99%